DETECTED LEVEL OF RECIDUES TETRACYCLINE IN BREAST MEAT, DRUMSTICK AND HEART OF CHICKEN WITH HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) - Winny Swastike (UNEJ e-Proceeding, 2012)
A method for determination of tetracycline (TC) residues in chicken meat has been established, validated and applied to study the residue level in broiler chicken meats which collected from chicken that given antibiotic synthetic (0,05 mg/kg fed). In total, 40 day old broiler chickenss were used in this experiment. They were allocated to 2 treatmants in 5 replicates with 4 broilers each. The Control of treatment was using basal diet and compared with TC in fed. Each diet was fed from day old to 35 days. TCs were extracted from chicken meat with McIlvaine-EDTA buffer solution and were cleaned-up with SPE C18 column cartridge and identified by an HPLC with photo diode array (PDA) detector. The analysis results showed that highest level of residues TC was in heart. Level residues of breast and drumstick were lower than residues in heart. But all of result were still higher than the regulated maximum residue level (MRL) of 0,1 mg/kg (SNI Number 01-63662000) therefore the breast meat, drumstick and heart of chicken in this research were not safe for human consumption.